Injury Pattern of FIFA, CAF and UEFA Soccer Tournaments: A Retrospective Study of Selected 2002 Matches (2004)
This retrospective study was undertaken to detail the injuries sustained by players in the 2002 event of the Federation of International Football Association (FIFA) male senior world cup, Confederation of African Football (CAF) male nations' cup and Union of European Football Association (UEFA) clubs championship competitions. This was aimed at determining the frequency, causes, severity and treatment modalities of injuries sustained in selected matches at these three competitions. Twenty-four matches (eight from each tournament) were randomly selected from the pool of matches played. Video tape footage of the selected matches was reviewed to assess the possible cause and severity of injuries, parts of the body injured and different lines of injury management undertaken during these tournaments. The data are presented using frequency, percentages and means. A total of III injuries were recorded. CAF matches had the highest occurrence of soccer injuries (42.34%). The knee was the most commonly injured part of the body in each of the three competitions (FIFA-23.5%, CAF-14.9% and UEFA-20.0%). Ice-massage therapy was used extensively in the three tournaments. Knee injuries were most commonly caused by tackling attempts. Most of the injuries sustained were minor and the leading immediate therapeutic intervention was cryotherapy.